Plant Developmental Biology - Biotechnological Perspectives - Davey, Michael R. (Berlin : Springer, 2010)
Many exciting discoveries in recent decades have contributed new knowledge to our understanding of the mechanisms that regulate various stages of plant growth and development. Such information, coupled with advances in cell and molecular biology, is fundamental to crop improvement using biotechnological approaches. Two volumes constitute the present work. The ?rst, comprising 22 chapters, commences with introductions relating to gene regulatory models for plant dev- opment and crop improvement, particularly the use of Arabidopsis as a model plant. These chapters are followed by speci?c topics that focus on different developmental aspects associated with vegetative and reproductive phases of the life cycle of a plant. Six chapters discuss vegetative growth and development. Their contents consider topics such as shoot branching, bud dormancy and growth, the devel- ment of roots, nodules and tubers, and senescence. The reproductive phase of plant development is in 14 chapters that present topics such as ?oral organ init- tion and the regulation of ?owering, the development of male and female gametes, pollen germination and tube growth, fertilization, fruit development and ripening, seed development, dormancy, germination, and apomixis. Male sterility and self-incompatibility are also discussed.
Includes references and subject index.
Keywords: Root development; Gametophyte development; Apomixis; 9